Role of Sabai Grass (Eulaliopsis binata) for Sustenance of Forest Protection Committee Members - Sarkar, Syamal Kumar; Chattopadhyay, R. N. (Indian Forester, 2001)
Non-Timber Forest Produce (NTFP) plays an Important role in the sustenance of the Forest Protection Committee members and that too on annual basis. Sabai grass is one such material which can be treated as forest produce by cultivating it as plantation intercrop and without interfering with the silviculture of the tree crop. In Nayagram block of West Midnapore Forest Division (West Bengal) Sabai is grown extensively both inside and outside forest areas. There is immense scope in value addition of this produce to augment the income of the protection committee members. That will also help the institutions to achieve economic viability. Rural Development Centre ofIndian Institute of Technology, Kharagpur is imparting training to Forest Protection Committee members on processing, value addition and exploring markets of the Sabai based products.